Structural Implications of Hydrogen-Bond Energetics in Membrane Proteins Revealed by High-Pressure Spectroscopy - Freiberg, Arvi (The Biophysical Society, 2012)
The light-harvesting 1 (LH1) integral membrane complex of Rhodobacter sphaeroides provides a convenient model system in which to examine the poorly understood role of hydrogen bonds (H-bonds) as stabilizing factors in membrane protein complexes. We used noncovalently bound arrays of bacteriochlorophyll chromophores within native and genetically modified variants of LH1 complexes to monitor local changes in the chromophore binding sites induced by externally applied hydrostatic pressure. Whereas membrane-bound complexes demonstrated very high resilience to pressures reaching 2.1 GPa, characteristic discontinuous shifts and broadenings of the absorption spectra were observed around 1 GPa for detergent-solubilized proteins, in similarity to those observed when specific (α or β) H-bonds between the chromophores and the surrounding protein were selectively removed by mutagenesis. These pressure effects, which were reversible upon decompression, allowed us to estimate the rupture energies of H-bonds to the chromophores in LH1 complexes. A quasi-independent, additive role of H-bonds in the α- and β-sublattices in reinforcing the wild-type LH1 complex was established. A comparison of a reaction-center-deficient LH1 complex with complexes containing reaction centers also demonstrated a stabilizing effect of the reaction center. This study thus provides important insights into the design principles of natural photosynthetic complexes.